Nilai-nilai Pendidikan Karakter Sosial dalam Al-Qur’an: Analisis Tematik terhadap QS. Al-Hujurat, An-Nur, dan Al-Ma’un - Widiana Putri Wulandari; Husein Aziz (IIQ An Nur Yogyakarta, 2026)
This study aims to analyze the values of social character education in the Qur'an through a thematic approach to QS. Al-Hujurat, An-Nur, and Al-Ma'un. These three surahs were chosen because they complementarily highlight social moral dimensions: Al-Hujurat emphasizes ethics and brotherhood, An-Nur emphasizes modesty and the preservation of honor, while Al-Ma'un emphasizes concern for the weak. The research method used is thematic analysis (maudu'i) by examining relevant verses and their interpretations. The analysis was conducted qualitatively to reveal social values that can be internalized in the context of Islamic education. The results of the study show that values such as ukhuwah (brotherhood), empathy, responsibility, modesty, and social solidarity form the basis for the formation of noble character. The three surahs teach that true faith must be manifested in ethical social behavior and caring for others. This study contributes to enriching the study of Islamic character education by offering an integration between moral, social, and humanitarian dimensions as the basis for shaping students' character.